An Emulation Model For Embedded Networks used in Avionics - Moya, Ramon Gómez; Corral, Pablo; Froes, Saulo M.; Lima, Antonio Cezar de Castro; de Barros Filho, Israel Eduardo; De Scals, Guillermo (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2019)
The objective of this document is to show how to create an emulation of an AFDX network with commercial switches. AFDX, is a standardized deterministic network which can be found inside big size aircrafts such as the Airbus A380 and the A350. This network is formed by End Systems and AFDX switches. The End systems are devices that send or receive data into or from the network. On the other hand, the AFDX switches are the devices which are responsible of the commutation of all the traffic. Throughout this paper we are going to map AFDX network features, using Cisco switches as AFDX switches and Linux computers as End Systems.